(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
The half-life is a unique property of radioactive isotopes used in a variety of applications including those of nuclear medicine. Researchers have proposed several empirical and semi-empirical models to obtain the alpha decay half-life of radionuclides. In this research, a formula was developed (A semi-empirical model), and fitted and applied to isotopes that decay according to alpha decay, in order to obtain their half-life. The results were in agreement with the experimental half-life data for radioisotopes of heavy alpha particles (HN) and super heavy isotopes (SHN), and the developed formula showed good agreement for light radioisotopes. The calculated standard deviation was /0.826/ for the radioisotopes used in nuclear medicine.